A Multi-national Comparison of Founding-Intention Factors - a Comparison of Germany, Argentina, United Kingdom and Latvia - Scheiner, Christian; Wassmus, Andreas; Sarmiento, T.; Richling, T.; Voigt, Kai-Ingo (International Council for Small Business (ICSB) World Conference, 2009)
LIM::209

Complexity Management in SMEs - Results from an Empirical Analysis in the German Machinery and Equipment Industry - Czaja, Lothar; Wassmus, Andreas; Voigt, Kai-Ingo (Production and Operations Management Society (POMS) Annual Conference, 2011)
LIM::257

Insights into the determinants of family business’ succession - Wassmus, Andreas; Schäfer, S.; Scheiner, Christian; Voigt, Kai-Ingo (International Council for Small Business (ICSB) World Conference, 2010)
LIM::240

Success Determinants for Product-related Service Innovations in the German Industry - Wassmus, Andreas; Voigt, Kai-Ingo; Müller, P. (European Association for Research on Services (RESER) International Conference, 2010)
LIM::238

The effects of customer orientation on the product performance of technological innovations: A comparison between SMEs and large companies - Voigt, Kai-Ingo; Baccarella, Christian; Wassmus, Andreas; Meissner, Oliver (Portland International Center for Management of Engineering and Technology (PICMET) Conference, 2011)
In a high-technology marketplace, consumers and producers simultaneously face a high uncertainty concerning these technological advanced products. Companies have to anticipate costumer demands way in advance to satisfy the market adequately. Among other things, this is the reason why there are failure rates among technological innovations as high as 65%, when these high-tech products are launched into the market. One way to counteract this fatal development is to integrate customers as early as possible in the product development process in order to achieve an optimal fit between market needs and technological possibilities. This study analyses customer orientation as part of market-orientation within the biggest German industrial markets. In this context, 108 managers were asked to answer a survey in order to find out about their companies' customer-integration methods, which are used to let the users be part of the product development process. In addition, this paper analyses the relationship between customer orientation, new product performance and company size. Surprisingly, correlation analysis shows that there is no significant relationship between customer orientation and new product performance in the group of small and medium-sized enterprises (SMEs), whereas this correlation is highly significant in the group of big companies. This fact leads to the conclusion that customer-orientation is not as important for SMEs as it is for larger companies. SMEs are by definition closer to the market. They have fewer customers and have to work side by side with them. In contrast, large companies have to compensate their lack of closeness by using customer orientation methods to boost product performance and, therefore, business performance. On the other side, SMEs have to concentrate on other ways to enhance their firm performance. © 2011 IEEE.

The effects of market and service-orientation on the success of solution providers in the German manufacturing sector - Voigt, Kai-Ingo; Wassmus, Andreas; Baccarella, Christian; Engel, Sebastian (Portland International Center for Management of Engineering and Technology (PICMET) Conference, 2012)
As a central aspect of the marketing concept is market orientation. However, the concept has been criticized, e.g. by pointing out that market orientation mainly concentrates on customer-focused activities, rather than on competitor-focused activities, what indicates towards an individualized product with high customer involvement. Especially in the manufacturing industry individualization in regard of a combination of products and services offers a huge differentiation factor. There has been a debate about the need for a shift from a product-centric view towards a service-dominant perspective. Hence, the concept of market-orientation has to be evaluated against this background. In addition, the authors argue that service-orientation has to be integrated in the concept, because of the growing importance especially for so-called solution provides with a focus on product/service-combinations. This study analyzes 173 companies in the German manufacturing industry to measure the effects of market- and service-orientation. In addition, we widened the well-known scale of Narver and Slater [57] including service-orientation. The results show that some aspects of market orientation can explain success of services. However, service-orientation seems not to have an effect on the success of new products, whereas implicit success factors of services a highly effected. © 2012 IEEE.